2023
DOI: 10.1177/10778012231188085
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Group Differences on Knowledge, Attitudes, and Perspectives of Coordinated Community Response Teams for Domestic Violence

Abstract: The goal of the mixed methods parallel design observational study was to examine belief, attitude, and knowledge differences among stakeholder groups in a coordinated community response team (CCRT). A second purpose was to assess the perceived strengths, weaknesses, and barriers to success of a CCRT for domestic violence (DV). Participants were members of a CCRT from victim advocacy, law enforcement, and court-affiliated agencies. Results demonstrate differences among stakeholder groups on myth acceptance, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The sample size also did not allow us to examine the differences in results based on specific job type. Previous research has shown that medical responders, fire fighters, and law enforcement hold different beliefs and are able to respond in different ways (Hetzel-Riggin, 2023). It will be important that follow-up work looks at the specific differences across first responder type.…”
Section: Limitationsmentioning
confidence: 99%
“…The sample size also did not allow us to examine the differences in results based on specific job type. Previous research has shown that medical responders, fire fighters, and law enforcement hold different beliefs and are able to respond in different ways (Hetzel-Riggin, 2023). It will be important that follow-up work looks at the specific differences across first responder type.…”
Section: Limitationsmentioning
confidence: 99%